Competing dynamics of intramolecular deactivation and bimolecular charge transfer processes in luminescent Fe(iii) N-heterocyclic carbene complexes. Issue 13 (9th March 2023) - Rosemann, Nils W.; Lindh, Linnea; Bolaño Losada, Iria; Kaufhold, Simon; Prakash, Om; Ilic, Aleksandra; Schwarz, Jesper; Wärnmark, Kenneth; Chábera, Pavel; Yartsev, Arkady; Persson, Petter
Abstract : Deactivation of an excited Fe III based dye has been investigated. Intramolecular deactivation is comparable to organic dyes, and ultrafast intermolecular deactivation via photoinduced disproportionation is observed over a range of low temperatures. Abstract : Steady state and ultrafast spectroscopy on [Fe III (phtmeimb)2 ]PF6 (phtmeimb = phenyl(tris(3-methylimidazol-2-ylidene))borate) was performed over a broad range of temperatures. The intramolecular deactivation dynamics of the luminescent doublet ligand-to-metal charge-transfer ( 2 LMCT) state was established based on Arrhenius analysis, indicating the direct deactivation of the 2 LMCT state to the doublet ground state as a key limitation to the lifetime. In selected solvent environments photoinduced disproportionation generating short-lived Fe(iv ) and Fe(ii ) complex pairs that subsequently undergo bimolecular recombination was observed. The forward charge separation process is found to be temperature-independent with a rate of ∼1 ps −1 . Subsequent charge recombination takes place in the inverted Marcus region with an effective barrier of 60 meV (483 cm −1 ). Overall, the photoinduced intermolecular charge separation efficiently outcompetes the intramolecular deactivation over a broad range of temperatures, highlighting the potential of [Fe III (phtmeimb)2 ]PF6 to perform photocatalytic bimolecular reactions.